RETRACTED: Navigating digital competence: Young people and AI technology expansion - Eflova Maria; Glebova Irina; Zakirov Ayaz (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001